Women involvement in development from Maqasid Syariah perspectives: a case study of Malaysian women - Mahmud, Mek Wok; Ghalia, Bouhedda; Abdul Aziz, Akhtarzaitie (IIUM Press, 2011)
This research is an attempt to discuss the issue of development and gender within the perspective of the predominant western as well as Islamic perspective. Moving from the Islamic perspective on development generally and women participation specifically, this work aims at providing some suggestions in the light of Islamic principles for the concept of human development in Islam, and identifying the guiding ideology behind's women involvement in development. In this relation, principles of Maqasid al Shari'ah will be thoroughly discussed with an objective of setting comprehensive principles and guidelines concerning the involvement of women in development. A case study on the experience of contemporary Muslim women in the fields of development in Malaysia will also be addressed. This study will contribute to the advancement of women and progress in all fields and acknowledge women's contribution at all levels.